PENGARUH PROMOSI, KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN TAMU BOBARA RESTAURANT DI GRAND WHIZ HOTEL MANADO - Sony Wijanarko; Tedy V Silape; Deabi Putri Walansendow (UPT Penelitian Sekolah Tinggi Ilmu Pariwisata Manado, 2025)
This research aims to determine the effect of promotions, service quality and facilities on guest satisfaction at Bobara restaurant at Grand Whiz Hotel Manado. The method used is a quantitative method with survey techniques, where data is collected by distributing questionnaires to 30 respondents who are restaurant guests. The independent variables in this research are promotion, service quality and facilities, while the dependent variable is guest satisfaction. Data analysis was carried out using multiple linear regression to test the relationship and influence between variables. The research results show that the three independent variables have a positive and significant effect on guest satisfaction at Bobara restaurant, both simultaneously and partially. These findings indicate that effective promotional strategies, good service and comfortable facilities contribute significantly to increasing restaurant guest satisfaction. The results of this research provide input for restaurant management to further improve promotional strategies, service quality and good facilities focused on increasing guest loyalty. Keywords: Promotion, Service Quality, Facilities, Guest Satisfaction